Exploring the influence of science lessons through text-based explanations and game-based explanations mixed with a socio-scientific approach on issues on students rational thinking ability and mistaken understanding - Kamarudin, Nurzatulshima; Ramadhan, Nurul Huda; Fadly, Wirawan; Suttiwan, Witsanu (Universitas Pendidikan Indonesia, 2024)
In both private and public education, several institutions may use game-based explanations. However, it does not rule out the possibility that most educational institutions use text-based explanations, which makes students tend to get bored because they only have to read and listen, so another alternative is needed: game-based explanations that can stimulate students' enthusiasm. Students improve their rational thinking abilities by adding a socio-scientific approach to reduce student misunderstandings. The method used in this research is a quantitative approach with a quasi-experimental design type of research. Hence, the research uses control and experimental classes for evaluation. The sample used was 29 students for the control class and 27 students for the experimental class. Based on the results obtained on rational thinking, the effect of conventions on rational thinking is 0.19, so there is no significant difference, and the post-test is 0.38, so there is a significant difference. In contrast, the effect obtained on the misunderstanding effect of conventions is 0.03. There is also no significant difference, but based on the average results of the experimental class, it is relatively superior to the control because the average of the experimental class is 83 and of the control class is 66, so game-based explanations are quite more influential than textbased explanations. This study offers insights into integrating multiple teaching methods to improve students' rational thinking skills, reduce misunderstandings, and make science learning more engaging.